Blind working time in visual display terminal users. Issue 2 (22nd January 2019) - Fujita, Hiroki; Sano, Kenji; Baba, Tomio; Tanaka, Tadashi; Ohno‐Matsui, Kyoko
Abstract: Objectives: Blind working (BW) time (time during which vision is not required), the interblink interval (IBI), and subjective symptoms were investigated in workers using visual display terminals (VDTs). Subjects and Methods: To investigate BW time, 10 VDT users were instructed to close their eyes when this did not interfere with their work. They were video recorded for 60 minutes using a webcam attached to the display on which they were engaged in regular data input tasks, and BW time was measured. The values of the IBI during the final 20 minutes of the BW experiment and during the final 20 minutes of normal working without BW were compared. A questionnaire was administered to investigate subjective symptoms using a visual analogue scale. Results: The total BW time during the final 20‐minute period was 20.6‐121.0 seconds (1.7%‐10.1%). The mean IBI of 5.5 ± 4.5 seconds during the BW experiment was not significantly different from that of 6.2 ± 5.6 seconds during normal working, and the mean of three IBIs immediately after BW during the BW experiment was 2.7 ± 1.0 seconds, significantly shorter than the 6.2 ± 5.6 seconds during normal working. Dry eye, ocular fatigue, and blurred vision during normal working improved when subjects were engaged in BW. Conclusions: VDT users could engage in BW during VDT work, the IBI was shorter immediately after BW, and subjective symptoms improved. These results suggest that BW may provide a more effective measure for the management of VDT working time.